Regional Economic Outlook, April 2022, Europe. (Regional Economic Outlook, 2022)
The war in Ukraine is casting a pall on Europe and its economy. Millions of innocent civilians have been displaced and thousands wounded or killed. For Europe's economy, it has struck at a time when private consumption and investment are still below pre-pandemic trends, and the pandemic itself continues to weigh on activity. Large increases in commodity prices and continued supply-side disruptions are now pushing inflation to higher levels, cutting into household incomes and firm profits. New risks loom from escalating fighting and disruptions to critical energy flows. The main challenges for Europe's policymakers are clear: caring for the refugees; helping vulnerable households and firms cope with higher spending on energy; beefing up energy security; and, together with social partners, ensuring that wage and price expectations remain well anchored.